2022
DOI: 10.1039/d2cc04288f
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous oxidation of I in water microdroplets and its atmospheric implications

Abstract: Atomic and molecular iodine, I• and I2, play important roles in the atmosphere, such as the catalytic depletion of ozone and the oxidation of gaseous elemental mercury. It’s known that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…23 It is postulated that there is a high electric field (∼10 9 V/m) at the surface of microdroplets that can pull electrons out of hydroxide ions, 27−30 for the abovementioned reduction reactions, 23−26 and the hydroxyl radical can cause oxidation reactions. 31,32 In some cases, reduction and oxidation reactions occurred simultaneously. 23 The redox potential at the air−water interface has been shown to be very different from the bulk, 33 and a recent study 34 shows that on the aerial surface of air bubbles in water, the oxidation potential of OH − to OH occurs is at least 0.7 V below redox tabled values due to the electrostatic destabilization of the hydroxide anion on water, which accelerates the formation of electrons and hydroxyl radicals at the air−water interface.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 It is postulated that there is a high electric field (∼10 9 V/m) at the surface of microdroplets that can pull electrons out of hydroxide ions, 27−30 for the abovementioned reduction reactions, 23−26 and the hydroxyl radical can cause oxidation reactions. 31,32 In some cases, reduction and oxidation reactions occurred simultaneously. 23 The redox potential at the air−water interface has been shown to be very different from the bulk, 33 and a recent study 34 shows that on the aerial surface of air bubbles in water, the oxidation potential of OH − to OH occurs is at least 0.7 V below redox tabled values due to the electrostatic destabilization of the hydroxide anion on water, which accelerates the formation of electrons and hydroxyl radicals at the air−water interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The power of water microdroplets to promote reduction chemistry has been demonstrated in the reduction of dissolved chloroauric acid to yield gold nanoparticles and nanowires, the reduction of doubly charged ethyl viologen to singly charged ethyl viologen, the reduction of organic compounds by hydrogenation, and the formation of the pyridyl anion in spraying an aqueous solution containing dissolved pyridine to form microdroplets . It is postulated that there is a high electric field (∼10 9 V/m) at the surface of microdroplets that can pull electrons out of hydroxide ions, resulting in an electron and a hydroxyl radical, and the electron is responsible for the abovementioned reduction reactions, and the hydroxyl radical can cause oxidation reactions. , In some cases, reduction and oxidation reactions occurred simultaneously . The redox potential at the air–water interface has been shown to be very different from the bulk, and a recent study shows that on the aerial surface of air bubbles in water, the oxidation potential of OH – to OH occurs is at least 0.7 V below redox tabled values due to the electrostatic destabilization of the hydroxide anion on water, which accelerates the formation of electrons and hydroxyl radicals at the air–water interface.…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that there is a high electric field (∼10 9 V/m) at the microdroplets’ surface due to either the formation of electric double layers or the alignment of the free O–H bonds of water molecules. This high field can even pull electrons out of hydroxide ions, resulting in an electron and a hydroxyl radical. The electron is responsible for the above-mentioned reduction reactions, and the hydroxyl radical can cause oxidation reactions or combine with others to form H 2 O 2 . In some cases, reduction by the electron and oxidation by OH were observed simultaneously for the same substrate molecules . It was also observed that, on the aerial surface of air bubbles in water, the oxidation potentials of OH – to OH occurred 0.7 V below redox tabled values as measured by electrochemical methods, so it should be easier for OH – to give up the electron at the air–water interface compared to the bulk.…”
mentioning
confidence: 99%
“…In the recent several years, water microdroplet chemistry is emerging as an exciting new field for the abilities to accelerate chemical reactions by several orders of magnitude compared to the same reactions in bulk water and to trigger spontaneous reactions that cannot occur in bulk water. , Among the unique properties of water microdroplets, the observation that water microdroplets exhibit strong reducing and oxidizing powers is especially intriguing. It is been postulated that there is a high electric field (∼10 9 V/m) at the surface of microdroplets either due to the formation of electric double layers or the alignment of the free O–H bonds of water molecules. This high field can even pull an electron out of a hydroxide ion, forming a hydroxyl radical and an electron (Figure ). The strong reducing power of water microdroplets is considered to be a result of the electron, and the oxidizing power of water microdroplets is a result of the hydroxyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…Since the electron and the hydroxyl radical coexist as shown in Figure , water microdroplets should presumably exhibit reducing and oxidizing powers simultaneously. However, most of the existing publications show either only reduction reactions or only oxidation reactions. This phenomenon might be a result of the redox properties of the substrates per se , since some compounds are easy to oxidize but difficult to reduce and some compounds are easy to reduce but difficult to oxidize. There have been only two cases , where reduction and oxidation reactions occurred simultaneously to the same substrate.…”
Section: Introductionmentioning
confidence: 99%